2012
DOI: 10.1128/aem.06123-11
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Population Structure of Brown Rot- and Moko Disease-Causing Strains of Ralstonia solanacearum Phylotype II

Abstract: The ancient soilborne plant vascular pathogen Ralstonia solanacearum has evolved and adapted to cause severe damage in an unusually wide range of plants. In order to better describe and understand these adaptations, strains with very similar lifestyles and host specializations are grouped into ecotypes. We used comparative genomic hybridization (CGH) to investigate three particular ecotypes in the American phylotype II group: (i) brown rot strains from phylotypes IIB-1 and IIB-2, historically known as race 3 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The data analyzed here are described in Cellier et al [39] (available at http://www.ebi.ac.uk/arrayexpress/experiments/E-MTAB-878). Briefly, 72 R. solanacearum strains were hybridized onto CGH pan-genomic microarrays.…”
Section: Methodsmentioning
confidence: 99%
“…The data analyzed here are described in Cellier et al [39] (available at http://www.ebi.ac.uk/arrayexpress/experiments/E-MTAB-878). Briefly, 72 R. solanacearum strains were hybridized onto CGH pan-genomic microarrays.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic data for nine new R. solanacearum strains also confirmed this classification (Remenant et al ., , , ). Thanks to the overwhelming phylogenetic data on phylotype II strains, it has been suggested that this phylotype should be divided into two subgroups IIA and IIB (Castillo and Greenberg, ; Cellier et al ., ). It cannot be excluded that deeper sampling in the other phylotypes may also result in a similar refinement of classification.…”
Section: A Classification Into Four Phylotypesmentioning
confidence: 97%
“…However, host specialization in the R. solanacearum species complex has rarely been described in detail. For example, pathogenicity tests under controlled conditions found that most Moko strains are also virulent to susceptible tomato and potato (Cellier et al, 2012). Many studies have been conducted to tentatively identify the genes associated with host specificity.…”
Section: Host Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Most BXW management practices were developed for moko disease, a bacterial wilt of banana caused by Ralstonia solanacearum phylotype II (Cellier et al ., ). Moko disease resembles BXW with respect to its epidemiology and the damage it causes (Thwaites et al ., ).…”
Section: Introductionmentioning
confidence: 97%